Multi‐omics identify xanthine as a pro‐survival metabolite for nematodes with mitochondrial dysfunction. (22nd February 2019) - Gioran, Anna; Piazzesi, Antonia; Bertan, Fabio; Schroer, Jonas; Wischhof, Lena; Nicotera, Pierluigi; Bano, Daniele
Abstract: Aberrant mitochondrial function contributes to the pathogenesis of various metabolic and chronic disorders. Inhibition of insulin/IGF‐1 signaling (IIS) represents a promising avenue for the treatment of mitochondrial diseases, although many of the molecular mechanisms underlying this beneficial effect remain elusive. Using an unbiased multi‐omics approach, we report here that IIS inhibition reduces protein synthesis and favors catabolism in mitochondrial deficient Caenorhabditis elegans . We unveil that the lifespan extension does not occur through the restoration of mitochondrial respiration, but as a consequence of an ATP‐saving metabolic rewiring that is associated with an evolutionarily conserved phosphoproteome landscape. Furthermore, we identify xanthine accumulation as a prominent downstream metabolic output of IIS inhibition. We provide evidence that supplementation of FDA‐approved xanthine derivatives is sufficient to promote fitness and survival of nematodes carrying mitochondrial lesions. Together, our data describe previously unknown molecular components of a metabolic network that can extend the lifespan of short‐lived mitochondrial mutant animals. Synopsis: Inhibition of insulin/IGF‐1 signaling (IIS), controlling a wide range of anabolic and catabolic processes, rescues C. elegans with dysfunctional mitochondria by altering energy homeostasis, favoring a metabolic status that depends on the AMPK/PKA axis and has xanthine accumulation as prominent metabolite fingerprint. Short‐lived mitochondrial‐mutant C. elegans display aberrant signaling networks that mainly converge to enhance IIS. IIS inhibition promotes survival of short‐lived mitochondrial‐mutant nematodes through metabolic rewiring. In animals carrying mitochondrial lesions, IIS inhibition diminishes protein synthesis and stimulates the AMPK and PKA activity. Xanthine derivatives improve survival and fitness of mitochondrial complex I‐deficient nematodes. Abstract : Inhibition of insulin signaling rescues mitochondrial dysfunction in C. elegans through metabolic rewiring centering on the AMPK/PKA axis and xanthine accumulation.